1998
DOI: 10.1111/j.1348-0421.1998.tb01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Immunological Analyses of the Flagellin of Clostridium tyrobutyricum ATCC 25755

Abstract: Abstract:The monoclonal antibody 21E7-B12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…(3) The flagellin of C. difficile has been reported to be post-translationally modified (Tasteyre et al 2000), and the modification is likely to be glycan, however, with significantly fewer putative glycosylation genes associated with the flagellin genes. The modification probably differs from that of C. botulinum, C. tetani, and C. acetobutylicum; (4) Flagellin glycosylation has also been reported in Clostridium tyrobutyricum (Arnold et al 1998). …”
Section: Components Of the Cell Surfacementioning
confidence: 99%
“…(3) The flagellin of C. difficile has been reported to be post-translationally modified (Tasteyre et al 2000), and the modification is likely to be glycan, however, with significantly fewer putative glycosylation genes associated with the flagellin genes. The modification probably differs from that of C. botulinum, C. tetani, and C. acetobutylicum; (4) Flagellin glycosylation has also been reported in Clostridium tyrobutyricum (Arnold et al 1998). …”
Section: Components Of the Cell Surfacementioning
confidence: 99%
“…The first reports of flagellin glycosylation in Clostridium species were for C. tyrobutyricum and C. acetobutylicum ATCC 824 (382)(383)(384). C. botulinum was the first human-pathogenic Clostridium species in which Oglycosylation of flagellin was studied.…”
Section: Protein Glycosylationmentioning
confidence: 99%
“…In contrast, Dons et al (11) determined that only a single flagellin gene was present within the genome and noted a discrepancy between the predicted and actual molecular weights of the L. monocytogenes flagellin. The flagellins from a number of gram-negative (5,14,15,21) and gram-positive (1,20) bacteria have previously been identified as glycosylated. Structural studies on both Campylobacter and Helicobacter flagella have shown that the flagellin structural proteins are posttranslationally modified at multiple sites with a novel sialic acid-like sugar, Pse5Ac7Ac, and related derivatives, via an O-linked glycosylation process (40,45).…”
mentioning
confidence: 99%